PERCEPTION OF PGSD STUDENT’S ON E-LEARNING DURING THE COVID-19 PANDEMIC - Dendy Dendy Saeful Zen (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to determine the perceptions of PGSD Study Program students towards e-learning-based learning during the covid 19 pandemic. The search method used is qualitative narrative. Data collection is performed from September 2021 to January 2021 for one semester to the semester of the academic year 2020-2021. With the completion of the non-form of monitoring for the realization of the lectures that take place every month, 3034 data were obtained which were completed by the students of the PGSD Study Program. The instrument used is in the form of a questionnaire, which is distributed through a non-form which is always completed by students on the 20th of each month. Assessed aspects include: 1) Students' assessment of the difficulty of conducting online lectures, the smallest assessment data being 13 or 0% stating Lack of quota. While the highest estimate is at 767 or 25% stating Difficulty in understanding the explanations because they do not meet face to face; Lack of understanding of using the application. 2). 2). Students' assessment of learning comfort using online data media The lowest grade is 11 or 0% stating Comfortable; Less comfortable, while the highest rating is at 1064 or 33% declaring quite comfortable. 3). Students' assessment of the quality of the Learning Management System (LMS) used by the data. The lowest grade is 66 or 2% stating that it is very poor, while the highest grade is 1316 or 43% saying good. 4). Students' assessment of the assignments given by the lecturers Small is 19 or 1% stating that the time is very short; The task is very difficult to perform; Educators do not comment on the work they are doing, while it is 734 or 24%. Time is very short. Based on the above explanation, it can be concluded that students' expectations for the implementation of e-learning are the existence of a stable server and an Internet network so that the entries do not err and there is a change in the login screen which is given a deeper explanation. Students hope that there will be more presentations of the teaching material and not be presented in an attractive form. There is a task assignment so that work on tasks and task collection are structured and not delayed. And students hope that each week there will be an evaluation of the assignments that have been done by the students to see if they are right or wrong.